Assessment of peer-conceptualised, written and led single-session group interventions for carers supporting a person with borderline personality disorder. (4th May 2022) - Brown, Rita; Heidari, Parvaneh; Taylor, Kaitlyn; Veltkamp, Joan; Broadbear, Jillian H.; Rao, Sathya
ABSTRACT: Objective: No research to date has investigated the utility of a single session peer-informed and peer-led intervention for carers of people with borderline personality disorder (BPD). Two single session format group interventions – a 2.5-hour information session and an all-day (7-hour) workshop – were conceptualised, written, and facilitated by a carer peer with the assistance of a clinician experienced in supporting people with BPD. This study aimed to evaluate the effectiveness of these interventions. Method: Participants completed the Burden Assessment Scale (BAS), Kessler-10 (K10) and the BPD attitude and knowledge survey (e-KALM) before and after the intervention as well as a set of questions seeking participants' thoughts about the usefulness of the content of the intervention and their overall satisfaction. Results: 225 carers who attended the 7-hour workshop and 100 carers who completed the 2.5-hour information session completed the pre-intervention survey. The carer participants' e-KALM scores improved significantly following interventions. Following the 7-hour workshop, K10 ( p < 0.05) and BAS ( p < 0.001) scores had a statistically significant improvement. Participants from both interventions reported that they appreciated the opportunity to be heard and supported and were very satisfied overall with the format and content. Discussion: Both single session carer intervention formats resulted in meaningful improvements in participants' knowledge about and attitudes towards BPD. The full-day workshop also reduced the perceived burden associated with care-giving; highlighting the community need for longer-term carer support.